The Legacy of a Hidden Camera: Acts of Making in Japanese-Canadian Internment Camps During the Second World War, as Depicted in Tom Matsui’s Photograph Collection - Read, Heather (Material Culture Review, 2016)
Abstract This paper adds to growing documentation of various object making practices that occurred during the internment of Japanese Canadians during the Second World War. The arts-informed research for the paper was conducted as part of the Landscapes of Injustice Project (LOI), which explores the dispossession of Japanese Canadian property during this time. In response to the massive loss of their possessions, out of necessity Japanese Canadians made gardens, furniture, and buildings, among other objects, while in camps. I share some diverse examples of camp-based making before deeply exploring the life and photographs of Tom Matsui. Tom’s photographs show evidence of making in camps, but are also material culture made in a camp. I suggest they have an important message of political resistance embedded in their creation.